Studi Deskriptif Fungsi Ekstrakulikuler Seni Tari Bagi Siswa SD Negeri 01 Kota Bengkulu - Ade Stevani; Dwi Anggraini; Resnani Resnani (Universitas Bengkulu, 2019)
This study aims to describe the fuction of extracurricular art of dance for students of SD Negeri 01 Kota Bengkulu. Type of qualitative research and descriptive naturalistic research method.the subject of this research is the extracurricular coach of dance art and the student of extracurricular activities of dance art. Data collection techniques use observation, interviews, and documentation. Data analysis is done by data reduction, data presentation (data display), data verification(coclusion drawing/verification) and withdrawal of conclusion (verification data). Testing the validity of the data using persistence of observation, membercheck and triangulation. The result of the research show the extracurricular function of dance which includes 1) development fuction, 2) sosialfuction, 3) rekreativefuction, the three fuctions have been done, but there are some indicators in the function of extracurricular art of dance that has not been done, that is development function in indicator the formation in indicator the formation of the character of discipline. In this indicator the formation of the character of students who follow extracurricular activities of dance art came too late because before the extracurricularschedule of dance art there are students who are still in the canteen and rest. Therefore, there should be a break between classroom hygiene activities and extracurricular activities of dance, so that the indicators of character building discipline are done.